The inceptionist’s guide to base editing: de novo PAM generation to reach initially inaccessible target-sites - Pakari, Kaisa; Wittbrodt, Joachim; Thumberger, Thomas (bioRxiv beta, 2022)
Base editing by CRISPR crucially depends on the presence of a PAM in proper distance to the editing-site. Here we present and validate an efficient one-shot approach termed “inception”, relaxing these constraints. This is achieved by sequential, combinatorial base editing: de novo generated synonymous, non-synonymous or intronic PAM-sites facilitate subsequent base editing at nucleotide positions inaccessible before, increasing the targeting range of highly precise editing approaches.
Gesehen am 26.02.2024